2015
DOI: 10.1590/0100-2945-192/14
|View full text |Cite
|
Sign up to set email alerts
|

COMPORTAMENTO IN VITRO DE Chalara paradoxa,AGENTE CAUSAL DA PODRIDÃO-NEGRA DO ABACAXIZEIRO, EM DIFERENTES CONDIÇÕES DE CULTIVO

Abstract: RESUMO-na pós-colheita do abacaxizeiro, a podridão-negra é considerada como um dos principais problemas na comercialização dos frutos. a doença é causada pelo fungo Chalara paradoxa (De Seynes) Sacc.. apesar da importância deste patógeno para a cultura, são poucas as informações relacionadas ao estudo do mesmo, com base em características fisiológicas in vitro. assim, o objetivo do trabalho foi avaliar o crescimento micelial, a esporulação e a germinação de C. paradoxa, em diferentes condições de cultivo. a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
1
1
2
Order By: Relevance
“…was in the PDA medium. In the present study, there were no differences between the three culture media tested for the sporulation of C. fimbriata, however in a study also performed by Souza (2015) with an anamorph of C. fimbriata, the largest sporulation obtained was in PDA medium.…”
contrasting
confidence: 72%
See 1 more Smart Citation
“…was in the PDA medium. In the present study, there were no differences between the three culture media tested for the sporulation of C. fimbriata, however in a study also performed by Souza (2015) with an anamorph of C. fimbriata, the largest sporulation obtained was in PDA medium.…”
contrasting
confidence: 72%
“…The isolates of C. fimbriata showed the highest values for mycelial growth in the PDA and V8-agar media, while Souza (2015) found that the greatest mycelial growth of the anamorph stage of Ceratocystis sp. was in the PDA medium.…”
mentioning
confidence: 91%
“…Culture media rich in carbohydrates play an important role in the mycelial growth of fungi, which use several nutritional sources for their growth and development, among these, sugars are the most necessary carbohydrates, useful for the growth, maintenance and reactivation of the fungus (Souza, et. al., 2015), thus requiring transfer to a medium that has cellulolytic materials as a substrate…”
Section: Fungal Reactivationmentioning
confidence: 99%
“…A qualidade e a intensidade de luz são fatores que podem afetar a germinação de conídios, a taxa de crescimento vegetativo e a indução de formação de estruturas reprodutivas. Para a maioria dos organismos, a luminosidade é um fator ambiental que regula o desenvolvimento e os processos de metabolismo (SOUZA et al, 2015). A temperatura é outro fator que exerce influência no crescimento, esporulação e germinação dos fungos (TEIXEIRA et al, 2001).…”
Section: Introductionunclassified
“…Griffon Maublque, que é polífago, sendo capaz de infectar, isoladamente ou em associação com outros patógenos, mais de 500 espécies vegetais (FREIRE;CARDOSO, 2003).A qualidade e a intensidade de luz são fatores que podem afetar a germinação de conídios, a taxa de crescimento vegetativo e a indução de formação de estruturas reprodutivas. Para a maioria dos organismos, a luminosidade é um fator ambiental que regula o desenvolvimento e os processos de metabolismo (SOUZA et al, 2015). A temperatura é outro fator que exerce influência no crescimento, esporulação e germinação dos fungos (TEIXEIRA et al, 2001).Os meios de cultura tem função importante no crescimento micelial de fungos fitopatogênicos.…”
unclassified